Toward Sustainability of Supply Chain by Applying Blockchain Technology - Daghighi, Ali; Shoushtari, Farzaneh (International journal of industrial engineering and operational research, 2023)
This research paper explores the application of blockchain technology in supply chain management to promote sustainability. With a growing emphasis on sustainability in today's business landscape, companies are seeking innovative solutions to reduce their environmental impact, improve social responsibility, and enhance transparency. Blockchain technology has emerged as a potential enabler, offering benefits such as enhanced traceability, transparency, and trust. This study provides an overview of the importance of sustainability in supply chain management and highlights the potential of blockchain to address sustainability challenges. It reviews existing literature on the application of blockchain in supply chain management, discussing its advantages and limitations. The paper also presents empirical findings obtained through case studies and data analysis, showcasing the impact of blockchain technology on sustainable supply chain management. The results demonstrate improvements in supply chain transparency, stakeholder engagement, waste reduction, and compliance with sustainability standards. The research concludes by summarizing the main findings and discussing the implications of blockchain adoption for organizations. It highlights the need for strategic planning and collaboration among supply chain stakeholders, while addressing the challenges and recommending areas for further research. Ultimately, this study contributes to the understanding of how blockchain technology can contribute towards achieving sustainability in the supply chain.